Investigation On The Mechanical Properties Of Glass Fiber Reinforced Polymer (Gfrp) Hybrid Composite With Eggshell Powder - Lee, Jie Shin (Universiti Sains Malaysia, 2019)
This research explores the utilization of chicken eggshell powder, ESP as a bio-filler material in E-glass fiber reinforced epoxy. Eggshell is the domestic and industrial by-product which usually being disposed as agriculture waste. Such filler usually has low density, highly abundant, inexpensive and exhibits as a good flame-retardant material. It can be developed in an attempt to increase the strength of composites and reduced the overall cost. The aim of the research is to perform mechanical test on the GFRP hybrid composite infused with eggshell powder (ESP). The powder size used are 100 microns and 150 microns. The influence of the filler concentration on composite materials was investigated by means of their tensile and compressive strength. The collected chicken eggshells were cleaned with clear water. The eggshells with membrane removed were then dried, crushed, pulverized and sieved to obtain the powder filler. The laminates were manufactured using wet hand lay-up, incorporating with ESP filler loading of 0, 10 %, 20 %, 30 % and 40 % by weight percentage for both of the powder size. The average fiber volume was 0.34. The finding reveals that composite with smaller filler size would result in a better strength for both tension and compression. The tensile strength and compressive strength has increased by 18% and 30% respectively with the addition of 10 wt. % of 100 μm ESP. The results acquired from this research reveal the potential of eggshell wastes to be channeled towards the production of value added composite materials for sustainable development.